Prognostic value of LI-RADS category on gadoxetic acid-enhanced MRI and 18F-FDG PET-CT in patients with primary liver carcinomas. - Min, Ji Hye; Kim, Seong Hyun; Hwang, Jeong Ah; Hyun, Seung Hyup; Ha, Sang Yun; Choi, Seo-Youn; Kim, Seon Woo; Kim, Hye Seung (European Radiology, 2021)
Objectives: To evaluate the postoperative prognostic value of the Liver Imaging Reporting and Data System (LI-RADS) category on gadoxetic acid-enhanced MRI and 18F-fluorodeoxyglucose PET-CT in patients with primary liver carcinomas (PLCs).Methods: A total of 189 patients with chronic liver disease and surgically proven single PLC (42 intrahepatic cholangiocarcinomas and 21 combined hepatocellular-cholangiocarcinomas and 126 hepatocellular carcinomas [2:1 matching to non-HCC malignancies]) were retrospectively evaluated with gadoxetic acid-enhanced MRI and PET-CT. Two independent reviewers assigned an LI-RADS category for each observation. The tumor-to-liver standardized uptake value ratio (TLR) was calculated. The overall survival (OS), recurrence-free survival (RFS), and the associated factors were evaluated.Results: In multivariable analysis, LI-RADS category (LR-4 or LR-5 [LR-4/5] vs. LR-M; OS, hazard ratio [HR] 2.24, p = 0.006; RFS, HR 1.61, p = 0.028) and TLR (low, < 2.3 vs. high, ≥ 2.3; OS, HR 2.09, p = 0.014; RFS, HR 2.17, p < 0.001) were the independent factors for OS and RFS. For the LR-M group, the high TLR group showed lower OS and RFS rates than the low TLR group (OS, p = 0.008; RFS, p < 0.001). For the LR-4/5 group, the OS and RFS rates were not significantly different between the high TLR and low TLR groups (both p > 0.05).Conclusions: Both LI-RADS category on MRI and TLR on PET-CT are associated with the postoperative prognosis of PLCs. The prognosis of PLCs classified as LR-M can be further stratified according to the TLR group, but not for the PLCs classified as LR-4/5.Key Points: • The LI-RADS category (LR-4/5 vs. LR-M) and tumor-to-liver standardized uptake value ratio (TLR, low vs. high) were independent factors for postoperative prognosis of primary liver carcinomas (PLCs). • For PLCs classified as LR-M, the TLR group helps stratify the postoperative prognosis of PLCs, with the high TLR group having a poor prognosis and the low TLR group having a better prognosis (p = 0.008 for OS and p < 0.001 for RFS). • For PLCs classified as LR-4/5, the OS and RFS rates were not significantly different between the high TLR and low TLR groups (both p > 0.05).